Characteristics of different groups of flare-CME in the minimum to rising phase of solar cycle 24 - N. Mohamad Ansor,; Z.S. Hamidi,; N.N.M. Shariff, (Universiti Kebangsaan Malaysia, 2023)
Coronal Mass Ejections are significant solar events that involve intense explosions of magnetic fields and mass particles out from the corona. As the hot plasma are brought by the solar wind into the Earth’s magnetosphere, geomagnetic storm is generated and causing malfunctions in telecommunication and power systems. This study is aimed to investigate the distribution of flare-CMEs characteristics which occurred at the beginning phase of solar cycle 24, from Dec. 2008 until Dec. 2013. In the analysis, all events are classified according to their class of flares associated with the CMEs. The CMEs that are accompanied by A, B, and C flares are categorized as low group flare-CME, while CMEs with M and X flares are placed under high group flare-CME. Afterwards, they are analyzed to observe the distribution of their main CME properties; velocity, acceleration and angular width. At the end of the study, we found that velocity and angular width are the two properties that have high influential for high and low groups, with R value of 0.36 and 0.67, respectively. Most of high group flare-CMEs showed up in 360° as well as low group flare-CMEs if the associated minor flares lasted longer than 30 min. Furthermore, the speed range of 360° high and low class flare-CME cannot be defined from the results since all of them propagated at fluctuating velocity. Hence, it is believed that full halo CMEs have no velocity boundary as they can travel from 500 km/s and go beyond 2500 km/s.